1994
DOI: 10.1093/hmg/3.2.355
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations of the connexin32 (GJB1) gene in X-linked dominant Charcot — Marie — Tooth neuropathy

Abstract: Ten families with X-linked dominant CMT neuropathy (CMTX1) were screened for point mutations of the connexin32 (Cx32, GJB1) gene. Two families showed missense mutations, respectively an A-->G transition at amino acid 102 (glutamate to glycine) and a C-->T transition at amino acid 142 (arginine to tryptophan). Three families showed nonsense mutations, respectively a C-->T transition at amino acid 22 (arginine to stop) a G-->T transversion at amino acid 186 (glutamate to stop), and a T-->A transversion at amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0
2

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(70 citation statements)
references
References 0 publications
3
65
0
2
Order By: Relevance
“…A correlation between Cx32 mutations and disease severity in CMTX has been suggested, but is still controversial in some aspects (Fairweather et al 1994;Ionasescu 1995;Ionasescu et al 1994Ionasescu et al , 1996Fischbeck et al 1996;Bone et al 1995Bone et al , 1997Janssen et al 1997;Birouk et al 1998;Sander et al 1998;Nelis et al 1999;Hahn et al 1999, Nicholson et al 1999. A dominant negative effect, loss of function effect, and interaction among different connexins have been proposed to explain the molecular mechanism of the genotype/ phenotype correlation in CMTX (Omori et al 1996;Deschênes et al 1997;Oh et al 1997;Ressot et al 1998;Sahenk and Chen 1998;Hahn et al 1999;Nicholson et al 1999;Fischbeck et al 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A correlation between Cx32 mutations and disease severity in CMTX has been suggested, but is still controversial in some aspects (Fairweather et al 1994;Ionasescu 1995;Ionasescu et al 1994Ionasescu et al , 1996Fischbeck et al 1996;Bone et al 1995Bone et al , 1997Janssen et al 1997;Birouk et al 1998;Sander et al 1998;Nelis et al 1999;Hahn et al 1999, Nicholson et al 1999. A dominant negative effect, loss of function effect, and interaction among different connexins have been proposed to explain the molecular mechanism of the genotype/ phenotype correlation in CMTX (Omori et al 1996;Deschênes et al 1997;Oh et al 1997;Ressot et al 1998;Sahenk and Chen 1998;Hahn et al 1999;Nicholson et al 1999;Fischbeck et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cx32 is a gap junction protein found mainly in the paranodal regions and the Schmidt-Lanterman incisures of peripheral nerve myelin; six connexin molecules assemble to form one connexon and act as gap junction channels providing direct intercellular communications (Bergoffen et al 1993;Scherer et al 1995). Since 1993, more than 200 different mutations, affecting every portion of the gene (Bergoffen et al 1993, Fairweather et al 1994Ionasescu 1995;Ionasescu et al 1994Ionasescu et al , 1996Bone et al 1995Bone et al , 1997Fischbeck et al 1996;Janssen et al 1997;Birouk et al 1998;Sander et al 1998;Nelis et al 1999;Hahn et al 1999), have been identified. However, only several mutations have been investigated in terms of their ability to form functional gap junctions and in terms of their relations with other connexins (Bruzzone et al 1994;Omori et al 1996;Deschênes et al 1997;Oh et al 1997;Ressot et al 1998;Sahenk and Chen 1998;Nicholson and Corbett 1999;Fischbeck et al 1999).…”
Section: X-linkedmentioning
confidence: 99%
“…Following the demonstration that mutations in connexin32 segregate with CMTX1 (Bergoffen et al 1993), other mutations have been described (Bergoffen et al 1993;Bone et al 1995a;Bruzzone et al 1994;Cherryson et al 1994;Fairweather et al 1994;Ionasescu et al 1994Ionasescu et al , 1995Orth et al 1994;Ressot et al 1996;Tan et al 1994Tan et al , 1996. These mutations reveal which parts of the connexin32 molecule are important for properly functioning gap junctions.…”
Section: Discussionmentioning
confidence: 99%
“…The mutations are summarized in Table 1. Three mutations at nucleotides 126, 249, and 477 have previously been described in presumably unrelated families (Bergoffen et al 1993;Fairweather et al 1994;Ionasescu et al 1994;Bone et al 1995a;Ressot et al 1996).…”
Section: Molecular Geneticsmentioning
confidence: 98%
See 1 more Smart Citation